Non-invasive observations on initial low frequency vibrations of the first heart sound--correlation with the 'presystolic' murmur in mitral stenosis. - Armstrong, T G (1978)
The initial low frequency component of the first heart sound, 'M', has been studied in normal subjects, and in patients with vario-s prosthetic mitral valves and with mitral stenosis, using simultaneous low frequency phonocardiography, echocardiography, and apex cardiography. The techniques showed 'M' to have a constant morphology in preisovolumic systole. In mitral stenosis, 'M' and the preisovolumic 'presystolic' murmur appear to be the same phonocardiographic phenomenon. While 'M' was present in sinus rhythm, augmentation of this normal vibration occurred particularly during the short cycles of atrial fibrillation. Leaflet coaption and movement of the ventricular wall as detected echocardiographically do not appear to play a role in its pathogenesis but the sound could emanate from the ventricular wall as it tautens and decreases its compliance at the onset of systole.